Repair and Maintenance Cost Estimation for Two Agricultural Tractors as Affected by Hours of Use and Years in Dongola Area, Sudan - Mohamed H. Dahab; Montasir A. Gafar; Abdul Gadir M. Abdul Rahman (Technological Innovation in Engineering Research Vol. 8, 2022)
Repair and maintenance cost is considered as one of the most important items for machinery reliability and management especially agricultural tractors. The current study was conducted in Dongola area, Sudan for the purpose of estimating tractor repair and maintenance expenses. The repair and maintenance (R&M) cost is an important item in the costs of ownership and operation. The information was gathered from Elshimalya Company for Agricultural Services records. In the study region, 44 tractors with two different power sizes—75 horsepower and 150 horsepower—were chosen. Regression correlation analysis was used to forecast the cumulative repair and maintenance (R and M) costs as a percentage of purchase price in connection to the cumulative hours of usage and age (years) for each tractor size as well as for the two sizes taken together based on the data gathered. Five model forms were developed (linear, logarithmic, polynomial, power, and exponential), and the power function was determined to be the best fit to explain the relationship. The accumulated Rand M costs as a percentage of the purchase price (Y) increased as the tractor’s accumulated hours of use (x) and age (g) in years climbed. The accumulated R&M cost was shown to have a significant association with both accumulated hours of use and tractor age in years (Average R2 = 0.93- 0.95). It was determined that the power function was the best fit for repair and maintenance cost estimations and this relation may be used as an average of the two tractor powers, for estimation of the accumulated R and M costs as percent of purchase price (Y) with accumulated hours of use (x) and age (g) as follows: Y=0.028x0.662 (mean), Y=12.294g1.276 (mean).